2018
DOI: 10.1007/s00181-018-1526-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urbanization on food demand in China

Abstract: Urbanization in China has been on a steady rise recently, which has contributed to the changing consumer food preferences and consumption patterns. This carries significant implications for food security in China and the global food trade, given the role China plays on global food markets. This study investigates the effects of urbanization on food demand in China by developing a structural framework that incorporates urbanization into a theory-plausible demand system. It also considers the effects of urbaniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 21 publications
1
50
0
Order By: Relevance
“…Previous literature predominantly focuses on quantity responses to changes in various socioeconomic and structural factors. Major findings indicate that consumers demand more meat, poultry, fish, dairy, and fruit at the expense of reduced demand for vegetables and staple grains once comprising the traditional Chinese food diet (Hovhannisyan and Devadoss, ; Hovhannisyan and Gould, ). More specifically, over the last three decades, grain and vegetable consumption has decreased by over 46% and 22.7%, respectively, while fruit consumption has increased almost by half, and meat consumption more than quadrupled in the same time period (e.g., Guo et al., ; Hovhannisyan and Gould, ; Xin et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature predominantly focuses on quantity responses to changes in various socioeconomic and structural factors. Major findings indicate that consumers demand more meat, poultry, fish, dairy, and fruit at the expense of reduced demand for vegetables and staple grains once comprising the traditional Chinese food diet (Hovhannisyan and Devadoss, ; Hovhannisyan and Gould, ). More specifically, over the last three decades, grain and vegetable consumption has decreased by over 46% and 22.7%, respectively, while fruit consumption has increased almost by half, and meat consumption more than quadrupled in the same time period (e.g., Guo et al., ; Hovhannisyan and Gould, ; Xin et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Major changes in food consumption patterns and shifts in composition of consumer diets have been a noteworthy phenomenon observed in many parts of the world in recent decades (Hovhannisyan and Devadoss, 2020;Hovhannisyan and Gould, 2011;Regmi, 2001;Sharma, Nguyen, and Grote, 2018). Some of the most important changes have been the increased consumer demand for organic, local, environmentally friendly, sustainable, and functional foods that offer benefits beyond basic nutrition (e.g., Kearney, 2010).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Consumers with convenient access to supermarkets appeared to consume more fruit but fewer vegetables [35], a finding that highlights the importance of the proximity of supermarkets in communities. The prevalence of modern supermarkets improved not only the availability of food but also and the standard of living, which boosted fruit consumption [48]. With regard to sales, consumers were found to prefer supermarket vegetables because they were monitored by supermarket management systems, which provided consumers with a diverse assortment of vegetables from multiple suppliers [33].…”
Section: Supermarketsmentioning
confidence: 99%
“…Studies have found that FVs sold at higher prices in urban locations [48,51,52]. In fact, a 10% increase in urbanization raised the price of vegetables by 0.9% and fruit by 0.7% [48].…”
Section: Urbanization and Inflation Of Fv Pricesmentioning
confidence: 99%